Traffic engineering in metro Ethernet. - Ali, M. (IEEE Network : the magazine of global information exchange)
Traffic engineering is a critical issue that has to be addressed in metro Ethernet networks for proper and efficient resource utilization as well as facilitating quality of service. This article aims at understanding the relevant issues and outlines novel algorithms for multipoint-TE in the metro Ethernet. We first propose a grouping scheme that extends the current label space in the provider domain and allows for a large number of VLANs to be provisioned efficiently. Next, the issues of load balancing, multiple spanning trees, and interaction between grouping and bandwidth provisioning are discussed, and solutions are provided. Finally, we address differentiated survivability in next-generation Ethernet and provide a novel scheme based on multiple spanning trees. The schemes proposed in this article are shown to be scalable, bandwidth-efficient, and practical for both the customer and the provider.